A colonização na pequena propriedade familiar pelo descendente de imigrante e o desenvolvimento socioeconômico de Concórdia (1920 a 1960) - Amador, Milton Cleber Pereira (Universidade do Vale do Rio dos Sinos, 2010)
The purpose of this thesis is to prove how happened the socioeconomic development in Concórdia city, Santa Catarina, from the colonization in a small familiar property through immigrants descendants, which built the base of agroindustry pattern that created Sadia industry. The research deals the year from 1920 to 1960, the period that beginning the process of colonization. In the region occurs the expansion and consolidation of agroindustry development pattern. The objective of the study is to analyze the total, which tried to understand the history of the city in context of brazilian and catarinense context. The investigation is based on written documents and oral sources. It was verified that Concórdia development did not suffer any rupture since the process of colonization until the agroindustry pattern in 1960s.
Keywords: Colonização; Pequena propriedade familiar; Descentente de imigrante; Desenvolvimento socioeconômico; Agroindustrial; Concórdia; Colonization; Small familiar property; Descendant of immigrant; Socioeconomic development; ACCNPQ::Ciências Humanas::História